Multilevel modeling of secure systems in QoP-ML - Ksįeżopolski, Bogdan (CRC Press, Taylor & Francis, 2015)
This book introduces the basis of the QoP modeling language along with all the advanced analysis modules, syntax, and semantics. It delineates the steps used in cryptographic protocols and introduces a multilevel protocol analysis that expands current understanding. Topics include: quality of protection evaluation of IT Systems; financial, economic, and CO2 emission analysis phase; multilevel analysis of cloud-based data centers; structures for advanced communication modeling and energy analysis; security and energy efficiency trade-offs for the protocols of wireless sensor network architectures; security metrics of cryptographic primitives; compares and contrasts QoP-ML with the PL/SQL, SecureUML, and UMLsec approaches by means of the SEQUAL framework